Techno-Economic Comparisons of HVAC and Simultaneous AC-DC Transmission. (17th January 2022) - Asmare, Lijalem Dires; Gessesse, Belachew Bantyirga; Getie, Elias Mandefro
Abstract : Electric power consumption has been increasing rapidly across the globe; this increase specially accelerated in the last decade. Consequently, existing transmission lines are becoming overloaded beyond their power transfer capability. The inadequacy of the transmission lines has contributed to power interruptions and instability of the power system. Construction of new transmission lines can be a solution to mitigate these problems. However, to build the whole structure of a new transmission line, a huge investment is required. Besides this, environmental concerns would create further barriers that delay the accomplishment of the project. Therefore, the effective and quickest solution to tackle this problem is enhancing the power transfer capability and stability margin of existing transmission lines. This paper studied the techno-economic feasibility of converting an existing HVAC line into a simultaneous AC-DC power transmission system to enhance power transfer capability as well as to improve power system stability. Using the proposed method, the loadability of Tana Beles to Addis Ababa 400 kV, 476.2 km AC line has increased to more than double which is from 1091.66 MW to 2196.85 MW. The active power loss and corona loss evaluation of the two systems ensured that simultaneous AC-DC system is more efficient than HVAC system. It is also shown that the instability can be effectively improved by simultaneous AC-DC power transmission with fast DC power modulation. From the economic point of view, rather than constructing new HVAC line, converting existing HVAC line into simultaneous AC-DC transmission system has a price reduction of about 107, 984, 968.56 USD or 32.46% of the new HVAC line cost. Considering a 35-year project life cost analysis, it is observed that the life cycle cost of the simultaneous AC-DC transmission system is about 29.2% lower than the life cycle cost of a new 400 kV HVAC line. Thus, the designed simultaneous AC-DC power transmission system has better technical performance and also is less costly than constructing a new HVAC line.